1998
DOI: 10.1002/(sici)1097-0231(19980630)12:12<763::aid-rcm229>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of ammonia in human breath by the selected ion flow tube analytical method using H3O+ and O2+ precursor ions

Abstract: We show how our selected ion flow tube mass spectrometric technique for trace gas analysis can be used to determine the concentrations of ammonia in alveolar breath from single exhalations using both H30+ and 02+ precursor ions for chemical ionization. Thus, data are presented of the alveolar ammonia concentrations in the breath of six healthy volunteers following the ingestion of a liquid protein meal, which show that consistent values are obtained using these two precursor ions. Alveolar breath ammonia conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…However, ionization under ambient conditions often also generates ions from other species present in the air. A classic example is ammonia (NH 3 ), which is ubiquitous in indoor air and comes from a number of sources including human breath where concentrations can range from 50 ppb to several hundred ppb . Although ammonia concentrations in laboratory air are generally much lower than those of water vapor, the PA of ammonia is higher (853.6 kJ mol −1 ), which results in the ionization of even trace levels of ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…However, ionization under ambient conditions often also generates ions from other species present in the air. A classic example is ammonia (NH 3 ), which is ubiquitous in indoor air and comes from a number of sources including human breath where concentrations can range from 50 ppb to several hundred ppb . Although ammonia concentrations in laboratory air are generally much lower than those of water vapor, the PA of ammonia is higher (853.6 kJ mol −1 ), which results in the ionization of even trace levels of ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…Selected ion flow tube mass spectrometry (SIFT‐MS) is now established as a reliable method to quantify trace gases in air with special attention to the quantification of trace gas metabolites in exhaled breath 14–25. SIFT‐MS is admirably suited to the measurement of ammonia in moist air samples such as exhaled breath, since the water vapour need not be removed before analysis, a procedure that probably partially removes ammonia 26. Hence, we have given much attention to the methodology of breath ammonia analyses using SIFT‐MS and shown that the collection of samples of breath into bags for off‐line analysis results in a loss of ammonia (and water vapour) to the bag surface and via diffusive loss through the bag material 11, 23, 26.…”
mentioning
confidence: 99%
“…SIFT‐MS is admirably suited to the measurement of ammonia in moist air samples such as exhaled breath, since the water vapour need not be removed before analysis, a procedure that probably partially removes ammonia 26. Hence, we have given much attention to the methodology of breath ammonia analyses using SIFT‐MS and shown that the collection of samples of breath into bags for off‐line analysis results in a loss of ammonia (and water vapour) to the bag surface and via diffusive loss through the bag material 11, 23, 26. Thus, we now recommend the use of direct on‐line analyses of ammonia, and indeed other trace gases, in individual exhalations of breath, a feature uniquely possible using SIFT‐MS instruments.…”
mentioning
confidence: 99%
“…We have validated the technique for ethanol on human breath and in the headspace above an aqueous ethanoic solution and blood (Wilson et al, 2001), where the SIFT–MS results were verified using known solution concentrations of ethanol and Henry's Law constant, and also using forensic procedures for ethanol vapor measurements. Also, Španel et al (1998) have quantified NH 3 on human breath using various ion precursors. Although the optimal sensitivity of the SIFT is 0.01 μL L −1 (10 ppb), in the present work, which used relatively fast sampling times, the reliable detection limit is estimated conservatively as 0.05 μL L −1 (50 ppb).…”
Section: Methodsmentioning
confidence: 99%